Advancing Climate Justice in Fiscal Governance: Redesigning Accountability Frameworks in Global Climate Finance - Azizov, Elman (SocioHumania: Journal of Social Humanities Studies, 2025)
This study examines how climate justice principles can be integrated into fiscal governance frameworks to enhance accountability within global climate finance. As climate change intensifies economic vulnerabilities, particularly in developing countries, the allocation and oversight of climate finance have become critical determinants of equity and resilience. Current fiscal oversight mechanisms exhibit notable progress in transparency but remain insufficient in addressing fairness, distributive justice, and participation. Through a comparative institutional analysis of global financial institutions, national budget systems, and emerging technological tools, this study identifies persistent challenges—including fragmented accountability structures, lack of standardized reporting mechanisms, and political-economy dynamics that hinder equitable funding flows. The findings emphasize that climate finance often prioritizes procedural compliance over transformative outcomes, limiting its potential to reduce structural inequalities and build adaptive capacity. The study argues that accountability frameworks must evolve beyond conventional financial auditing, incorporating social and environmental metrics that reflect the moral imperatives of climate justice. By integrating participatory governance, digital innovations, and harmonized reporting standards, fiscal systems can foster more transparent, just, and impactful climate finance. This research contributes to the discourse on climate governance by proposing accountability reforms capable of linking financial decision-making with ethical considerations, thereby advancing global efforts toward a fair and resilient climate transition.